In between coral branches: describing the courtship behavior of the Mediterranean cardinalfish Apogon imberbis (Linnaeus, 1758) - GREGORIN, CHIARA; COPPARI , MARTINA; MARROCCO , TEO; PULIDO MANTAS , TORCUATO; ROVETA, CAMILLA; WILLIS, TREVOR J.; CERRANO, CARLO (Mediterranean Marine Science, 2025)
The behavior of a pair of cardinalfish Apogon imberbis (Linnaeus, 1758) (Apogonidae) was investigated through the acquisition of time-lapse images at three-min-intervals over five consecutive days, encompassing both diurnal and nocturnal hours. We characterized the phases of courtship, quantified the frequency and alternation of activity patterns, and assessed their duration across the diel cycle, highlighting potential differences between sexes. The habitat preferences by A. imberbis associated to the red octocoral Paramuricea clavata (Risso, 1827) (Cnidaria, Anthozoa) were documented for the first time in the Mediterranean Sea. The pair exhibited pronounced diel behavioral patterns, with increased nocturnal activity likely linked to zooplankton foraging, and diurnal rest in shelters provided by the coral branches. The courtship consisted in three activities that were cyclically repeated throughout the day, with a total duration of 10.2 hours. The novel behavior named “patrolling” was played by the female after the mating event, presumably linked to the egg-laying site defense. The time-lapse technique offers the possibility to collect continuous, non-invasive observations at great depths and for prolonged periods, allowing for detailed surveys of the organisms, their interactions and the use of the habitat. The advantages and potentialities of this methodology could be further improved by machine learning programs for the recognition of animal activity patterns, allowing for the processing of massive dataset, reducing human workload and improving accuracy and time-efficiency.